Penyuluhan Anemia pada Ibu Hamil di Klinik Abi Ummi Dw Sarmadi Palembang - Ratna Dewi; Erike Septap Prautami; Humaira Humaira; Putri Anggraini (COVIT (Community Service of Health), 2021)
Anemia in pregnancy is a condition where the hemoglobin level in the blood is below normal, namely the hemoglobin level <11 g/dl. Anemia in pregnancy can cause fatigue, weakness, decreased appetite, frequent dizzy vision, dizziness and pale lips, this is caused by a lack of nutrients for blood formation, such as iron deficiency, folic acid and vitamin B12. Anemia that often occurs in pregnant women is anemia due to iron (Fe) deficiency. Anemia is one of several factors that cause maternal death. In pregnant women, anemia increases the frequency of complications in pregnancy, childbirth, the risk of maternal death, prematurity, low birth weight, and perinatal death. Anemia can also cause antepartum and post partum bleeding. Counseling about anemia in pregnant women is an effort to increase the knowledge of pregnant women to meet nutritional needs so as to avoid anemia in pregnancy. The purpose of community service activities is to provide knowledge about anemia and how to prevent anemia in pregnancy. Counseling methods with lectures and questions and answers to pregnant women. Conclusion pregnant women understand how to prevent anemia in pregnancy. It is suggested to health workers, especially the Dr. Sunedi clinic, to provide more frequent health education about anemia to pregnant women in early pregnancy and to check hemoglobin levels so that symptoms of anemia are detected immediately and can be prevented. Keywords: Anemia, pregnant women